The neuromuscular characteristics of gymnasts' jumps and landings at particular stages of sports training - Niespodzinski, B.; Grad, R.; Kochanowicz, A.; Mieszkowski, J.; Marina, M.; Zasada, M.; Kochanowicz, K. (Journal of Human Kinetics, 2021)
Safe and proper landings are crucial elements of gymnastics events. Long-term training leads to specific neuromuscular adaptations which are yet to be explored in terms of gymnastic landings. The aim of the study was to assess differences in landings` neuromuscular characteristics between gymnasts at three subsequent gymnastic training stages and age-matched non-athletes. Forty-six gymnasts (G) and 58 controls (C) performed countermovement jumps on a force plate with simultaneous surface electromyography (SEMG) of lower body muscles, measured during the pre- (100 ms) and post-landing phase (0-100 and 0-200 ms). Three age groups participated in the study: 8-10 (G1, C1), 12-14 (G2, C2), 18-25 (G3, C3) years. Analysis included the normalized root mean square (NRMS) SEMG signal and ground reaction forces (GRFs). Gymnasts achieved 13% higher values (p = 0.04) of relative peak GRFs in comparison with controls. It was especially seen in 8-10-year-olds: G1 presented 33% higher (p = 0.03) results than C1 and G2. In SEMG analysis, gymnasts showed overall lower NRMS values in comparison with the controls. In the pre-landing phase, the NRMS in the rectus femoris was from 1.6 up to 3.4 times higher for C1 (p = 0.02) than for C2, G2, C3, and G3. Gymnasts across subsequent training stages exhibit different patterns of neuromuscular coordination during landings. The highest GRF observed in the youngest gymnasts may be a potential risk factor of injuries. Therefore, further injury-focused investigation is recommended to monitor landing strategies among gymnasts of different stages with particular emphasis on the beginners.